Environment and development in Bangladesh : V.1 - Rahman, A. Atiq.; Haider, Raana; Jansen, Eirik, G. (Dhaka, Bangladesh : University Press, 1994)
Contributed articles.
Includes bibliographical references.
Keywords: Environmental policy -- Bangladesh; Human ecology -- Bangladesh